Cinema in service of the state : perspectives on film culture in the GDR and Czechoslovakia, 1945-1960 - Karl, Lars 1973- HerausgeberIn; Skopal, Pavel 1972- HerausgeberIn (Film Europa, 2015)
The national cinemas of Czechoslovakia and East Germany were two of the most vital sites of filmmaking in the Eastern Bloc, and over the course of two decades, they contributed to and were shaped by such significant developments as Sovietization, de-Stalinization, and the conservative retrenchment of the late 1950s. This volume comprehensively explores the postwar film cultures of both nations, using a "stereoscopic" approach that traces their similarities and divergences to form a richly contextualized portrait. Ranging from features to children's cinema to film festivals, the studies gathered here provide new insights into the ideological, political, and economic dimensions of Cold War cultural production.